Update on the rational use of (90)Y-ibritumomab tiuxetan in the treatment of follicular lymphoma - Lehnert, Martina (Dove Medical Press, 2009)
The development of radiolabeled antibodies against CD20 has facilitated targeted treatment of follicular lymphoma (FL). By using (90)Y-ibritumomab tiuxetan (Zevalin(®)), a radionuclide (yttrium-90, linked by the chelator tiuxetan to the antibody ibritumomab) is brought into the vicinity of lymphoma cells. By the so-called cross-fire effect, this beta emitter has the capacity to destroy not only the lymphoma cells having bound the antibody, but also neighboring lymphoma cells. Currently this antibody is licensed in the European Union for use in relapsed or refractory FL. It is anticipated that this drug will also be approved for use as consolidation therapy after successful first-line treatment. Here we first will review the published literature supporting the use of (90)Y-ibritumomab tiuxetan in the aforementioned indications and emerging data showing applicability of ibritumomab tiuxetan as sole first-line therapy for FL, as well as in the transplant setting. Possible strategies of incorporating ibritumomab tiuxetan into the treatment algorithm of FL are discussed.